Copper (II), Cobalt (II) and Chromium (III) Complexes of 2, 4 Diamino-5- (3, 4, 5 Trimethoxy-Benzyl) Pyrimidine: Synthesis, Charecterisation and Influence of Copper (II) Complex On Germination of Legume Seeds - DILIP. R. KULKARNI; MUKUND. R. MULEY; JIJABHAU. K. RODGE; MADHAVRAO. N. DESHPANDE; SWATI. S. ARDHAPURKAR (International Journal of Pharma and Bio Sciences, 2010)
Cu(II), Co(II)and Cr(III) complexes of 2, 4 diamino–5 (3, 4, 5 Trimethoxy benzyl) pyrimidine have been synthesized and characterized by elemental analysis, molar conductivity, magnetic moments, IR, 1HNMR, UV-visible, EPR, TG/DTA and powder XRD. Copper complex had 1:1 stoichiometrty where as cobalt and chromium complexes have 1:2 stoichiometries. The influence Cu(II) complex on germination of Bengal gram (Cicerarientinum) (Dollar), Groundnut (Arachis hypogaea) (SB XI), Soyabean (Glycine max)(Clark) and Pea(Pisumsativaum) (Aarkil)seeds from local Varieties have been investigated. Complex was found to exhibit enhanced activity compared to ligand TBPD and metal salts.